Myoclonic Epilepsy: Case Report of a Mild Phenotype in a Pediatric Patient Expanding Clinical Spectrum of KCNA2 Pathogenic Variants - Perilli, Lorenzo; Mastromoro, Gioia; Murciano, Manuel; Amedeo, Ilaria; Avenoso, Federica; Pizzuti, Antonio; Guido, Cristiana Alessia; Spalice, Alberto (Frontiers in Neurology, 2022)
We report on the rare case of a male toddler presenting with myoclonic epilepsy characterized by daily episodes of upwards movements of the eyebrows, and myoclonic jerks of both head and upper limbs. He also showed speech delay, tremors and lack of motor coordination. Next Generation Sequencing analysis (NGS) performed in trio revealed in the proband the c.889C>T de novo missense variant in the KCNA2 gene in heterozygous state. This is the first case of myoclonic epilepsy in a toddler due to a c.889 C>T KCNA2 missense variant. He was treated with valproic acid and ethosuximide with a good clinical response. At 6 years old, follow-up revealed that the proband was seizure-free with tremors and clumsiness in movements. According to the literature, this case supports the correlation between myoclonic epilepsy and KCNA2 alterations. This evidence suggests performing genomic testing including the KCNA2 gene in preschool patients affected by myoclonic epilepsy, especially when associated with delayed neurodevelopment. Our goal is expanding the phenotypical spectrum of this rare condition, adding clinical features following a genotype-first approach.